2011
DOI: 10.3892/etm.2011.352
|View full text |Cite
|
Sign up to set email alerts
|

Beyond free radical scavenging: Beneficial effects of edaravone (Radicut) in various diseases (Review)

Abstract: Abstract. Free radicals play an important role in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 69 publications
0
45
0
Order By: Relevance
“…The natural antioxidants such as β-carotene, 28 a terpenoid constituent of the crude extract can ameliorate the nephrotoxicity by its free radical scavenging activity. Edaravone, is a synthetic-free radical scavenger 6 besides its potent free radical scavenging effects, edaravone possesses anti-apoptotic and anti-necrotic effects in animal models of various diseases. 7 Edaravone possess nephroprotective property by promoting antioxidant enzyme system, thereby attenuating ROS generation and lipid peroxidation as similar to Wongmekiat et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The natural antioxidants such as β-carotene, 28 a terpenoid constituent of the crude extract can ameliorate the nephrotoxicity by its free radical scavenging activity. Edaravone, is a synthetic-free radical scavenger 6 besides its potent free radical scavenging effects, edaravone possesses anti-apoptotic and anti-necrotic effects in animal models of various diseases. 7 Edaravone possess nephroprotective property by promoting antioxidant enzyme system, thereby attenuating ROS generation and lipid peroxidation as similar to Wongmekiat et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…5 Edaravone is chemically known as 3-methyl-1-phenyl-2-pyrazolin-5-one, it is a synthetic-free radical scavenger. 6 It was the first neuroprotective drug to be introduced in worldwide by Japan in treating patients with cerebral infarction. 6 Moreover it's has a potent free radical scavenging effects, edaravone possesses anti-necrotic and anti-apoptotic effects in varies diseases of animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings indicate that edaravone may be useful for the treatment of patients with AIS, due to its being involved in inhibiting the deleterious molecular events associated with brain injury. Beyond AIS, edaravone has also been reported to have diverse protective effects against the ischemic injury of various other organs in several animal disease models (30)(31)(32)(33)(34).…”
Section: Edaravonementioning
confidence: 99%
“…It has been shown to exhibit neuroprotective effects against oxidative stress in patients with cerebral infarction and acute ischemic stroke (Yoshida et al 2006). In vivo and in vitro studies have found that edaravone has a neuroprotective effect in animal models of amyotrophiclateral sclerosis and Parkinson's disease (Kikuchi et al 2012). We hypothesized that edaravone, a substance with known neuroprotective effects, might have protective effects in mania in an animal model of BD.…”
Section: Introductionmentioning
confidence: 99%